On Special Weakly Ricci-Symmetric Kenmotsu Manifolds - Aktan, Nesip; Gorgülü, Ali; Özüsağlam, Erdal (Sarajevo Journal of Mathematics, 2024)
In this paper, we have studied special weakly Ricci symmetric Kenmotsu manifolds. We show that if a special weakly Riccisymmetric Kenmotsu manifold admits a cyclic parallel Ricci tensor then the associate 1–form α must be zero. On the other hand we show that a special weakly Ricci-symmetric Kenmotsu manifold can not be an Einstein manifold if the associate 1–form α eq 0 and Ricci tensor of a special weakly Ricci-symmetric Kenmotsu manifold is parallel. 2000 Mathematics Subject Classification. 53C21, 53C25